Synthesis, characterization, DFT study, conductivity and effects of humidity on CO2 sensing properties of the novel tetrakis- [2-(dibenzylamino)ethoxyl] substituted metallophthalocyanines - DUMLUDAĞ, FATİH; ÖZER, METİN (ELSEVIER SCIENCE SA, 2020)
Novel tetrakis[2-(dibenzylamino)ethoxyll substituted nickel (II), cobalt (II) and manganese (II) phthalocyanines were synthesized by using 4-(2-(dibenzylamino)ethoxy)phthalonitrile with corresponding metal salts in 2-N, N-dimethylaminoethanol. New phthalonitrile ligand was prepared from 2-(dibenzylamino)ethan-l-ol and 4-nitrophthalonitrile in acetonitrile at reflux temperature using potassium carbonate as catalyst. The compounds was characterized by elemental analysis, infrared, ultraviolet-visible and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopic methods. Density functional theory calculations were performed for structural and electronic properties. Direct current and alternating current conductivity properties of the metallophthalocyanine films were investigated between 293 - 523 K and frequencies 40 -100 kHz. The direct current conductivity values were calculated as 5.29 x 10(-10 )S/cm, 2.39 x 10(-9)S/cm, and 3.04 x 10(-10) S/cm, for nickel, cobalt and manganese complexes (293 K) films, respectively. Activation energies of the films were 0.50-0.70 eV for T < 478 K. Alternating current conductivity results suggest that hopping model explains dominant charge transport mechanisms. Carbon dioxide sensing properties (1000-8000 ppm) of the metallophthalocyanine films were investigated at room temperature (293 K) in air as background. Additionally, effects of the relative humidity on carbon dioxide sensing properties were also investigated for relative humidity between 0-80 % RH in air. Response and response time values of the films were reported. Newly synthesized phthalocyanine complexes in this study were found to be reversible and sensitive to the carbon dioxide gas in humid air. Carbon dioxide sensing measurements revealed that sensitivity of the sensors increased with increasing carbon dioxide concentration and relative humidity. It is found that manganese phthalocyanine showed greater sensitivity than nickel- and cobalt phthalocyanine complexes.
Keywords: Phthalocyanine; MALDI-TOF MS; Density functional theory; Semiconductor; Conductivity; CO(2 )sensing; GAS; PHTHALOCYANINES; DEVICE